Myelodysplasia and Mast Cell Leukemia with t(9;22) - Kathryn J. Lago; Matthew P. Shupe; William N. Hannah; Gopalrao V. N. Velagaleti; Christina Mendiola; Veronica Ortega; Brian R. Haney (Case Reports in Oncological Medicine, 2017)
Introduction. Mast cell leukemia (MCL) is a rare variant of systemic mastocytosis. Most cases of mast cell leukemia do not have cytogenics performed. Furthermore, there is no consistent chromosomal abnormality identified in MCL. This is the first reported case of MCL with a (9;22) translocation. Case Report. An 80-year-old female presented with pancytopenia and was diagnosed with MDS. Over time, she required hospitalizations for platelet transfusions with increased frequency. She developed fatigue and weakness along with gastrointestinal symptoms. On exam, she had diffuse abdominal tenderness and a maculopapular rash. Her lab results revealed a new basophilia. A bone marrow biopsy showed 100% cellularity with many aggregates of mast cells. Chromosomal analysis showed t(9;22) with confirmed BCR/ABL1 fusion by fluorescence in situ hybridization (FISH). Discussion. MCL has a poor prognosis due to the aggressive nature of the disease and ineffective therapies. Translocation (9;22) is known to be associated with MDS transformations to acute leukemia; however, this translocation has never been reported in MCL. Further research on the relationship between t(9;22) and MCL could lead to development of improved therapeutic options.